Exploring the Role of Religious Moderation in Islamic Education: A Comprehensive Analysis of Its Unifying Potential and Practical Applications - Mala, Asnal; Hunaida, Wiwin Luqna (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This study aims to explore the role of religious moderation within Islamic Education as a unifying force in diverse societies. Employing a qualitative library research approach, this investigation delves into the concept and implementation of religious moderation, seeking to understand how it can foster moderate religious attitudes and mitigate tensions within pluralistic communities. The article encompasses an analysis of various sources, including perspectives from the Qur’an and Hadith, as well as a wide range of related literature. These sources, including books, journals, and other relevant materials, were collected and analyzed to produce a scholarly article. The findings suggest that religious moderation holds significant potential to bridge differences and cultivate unity in multicultural societies. The study highlights the necessity for a more comprehensive approach to Islamic education that incorporates the principles of religious moderation into the curriculum. Additionally, an understanding of religious moderation is also crucial at the family, community, and higher education levels to develop attitudes of tolerance and a balanced approach to religious life. This research aims to contribute additional insights into the concept and implementation of religious moderation within the context of Islamic Education and its potential to act as a cohesive and unifying element in diverse communities.Education and how it can contribute as an adhesive and unifier in a diverse society.